The extracellular vesicle-based treatment: a developing strategy for periodontal diseases - Zhang, Xuan; Gao, Hanyu; Lin, Li (Frontiers in Immunology, 2025)
Periodontitis, a chronic inflammatory disease, is characterized by irreversible bone resorption, persistent attachment loss, and even ultimate tooth loss. The individual quality of life and the public burden of health are greatly impacted by the destruction of periodontal tissue and the lack of effective treatment. Exploration into how the inflammatory and damaged structure changes into the healthy and regenerative tissue is one of the most fascinating subjects in this field. A novel approach is the application of a nanoparticle, extracellular vesicle, which originates from natural or engineered cells. To further exploit its full potential, scientists have conducted massive studies into its biological and functional mechanisms. This review provides an overview of current extracellular vesicle-based treatments on periodontal diseases. It begins with summarizing the history of periodontal regeneration. Then, this article takes a general overview of extracellular vesicle’s biological characteristics, structures and current achievements. After that, we discussed extracellular vesicle’s functions in periodontium. In addition, this study also embraces a diverse range of extracellular vesicle-based strategies, a general workflow for EVs’ periodontal application. Finally, the challenges and prospects of the extracellular-based therapy have been discussed.